The Wage Effects of Offshoring: Evidence from Danish Matched Worker-Firm Data - Hummels, David; Jørgensen, Rasmus; Munch, Jakob; Xiang, Chong (American Economic Review, 2014)
We employ data that match the population of Danish workers to the universe of private-sector Danish firms, with product-level trade flows by origin- and destination-countries. We document new stylized facts about offshoring and instrument for offshoring and exporting. Within job spells, offshoring increases (decreases) the high-skilled ( low-skilled) wage; exporting increases the wages of all skill-types; the net wage-effect of trade varies substantially within the same skill-type; conditional on skill, the wage-effect of offshoring varies across task characteristics. We estimate the overall effects of offshoring on workers' present and future income streams by constructing pre- offshoring-shock worker-cohorts and tracking them over time. (JEL F14, F16, J24, J31, L24)